Practical considerations for spirometry during the COVID-19 outbreak: Literature review and insights - Crimi, Claudia; Impellizzeri, Pietro; Campisi, Raffaele; Nolasco, Santi; Spanevello, Antonio; Crimi, Nunzio (Pulmonology, 2021)
As the Coronavirus disease 2019 (COVID-19) is spreading worldwide, countries are dealing with different phases of the pandemic. Lately, scientific evidence has been growing about the measures for reopening respiratory outpatient services during the COVID-19 pandemic. We aim to summarize the key differences and similarities among recommendations by different national and international organizations. We searched on Google and Pubmed for recently published National and International Recommendations/Guidelines/Position Papers from professional organizations and societies, offering a guidance to physicians on how to safely perform pulmonary function testing during COVID-19 pandemic. We also searched for spirometry manufacturers' operational indications. Indications on spirometry were released by the Chinese Task force, the American Thoracic Society, the European Respiratory Society, the Thoracic Society of Australia and New Zealand, the Société de Pneumologie de Langue Française, the Spanish Societies (Sociedad Espanola de Neumologia y Cirugia Toracica, Sociedad Espanola de Alergologia e Inmunologia Clinica, Asociacion de Especialistas en Enfermeria del trabajo, Asociacion de Enfermeria Comunitaria), the Sociedade Portuguesa de Pneumologia, the British Thoracic Society/Association for Respiratory Technology & Physiology, the Irish Thoracic Society, the Sociedad Uruguaya de Neumologia, the Italian Thoracic Society and the Italian Respiratory Society, Cleveland Clinic and Nebraska Medical Center. Detailed technical recommendations were found on manufacturers’ websites. We found several similarities across available guidelines for safely resuming pulmonary function services, as well as differences in criteria for selecting eligible patients for which spirometry is deemed essential and advice which was not homogenous on room ventilation precautions. This study shows a synthesis of national/international guidelines allowing practicing physicians to adapt and shape the way to organize their outpatient services locally. There is generally good agreement on the importance of limiting pulmonary function testing to selected cases only. However, significant differences concerning the subsets of candidate patients, as well as on the management of adequate room ventilation, were observed.